2013
DOI: 10.1111/codi.12090
|View full text |Cite
|
Sign up to set email alerts
|

One‐year outcome of haemorrhoidectomy: a prospective multicentre French study

Abstract: Complications of open haemorrhoidectomy were infrequent. Anal continence was not altered. Comfort and well-being were significantly improved at 1 year after surgery. Patient satisfaction was high despite residual anal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 27 publications
(32 reference statements)
2
19
3
2
Order By: Relevance
“…In this study QOL significantly improved following fistulotomy, and returned to that of the general population when continence deterioration was small; similar results have been found using SF-36 for other benign anorectal conditions such as haemorrhoid surgery [32] and anal fissure [33]. Using a GI disease-specific QOL questionnaire, the GIQLI [34], a similar result has been found with patients undergoing surgery for recurrent fistula [35], suggesting that the benefits of successful surgery may outweigh the risks of reduced continence.…”
Section: Discussionsupporting
confidence: 83%
“…In this study QOL significantly improved following fistulotomy, and returned to that of the general population when continence deterioration was small; similar results have been found using SF-36 for other benign anorectal conditions such as haemorrhoid surgery [32] and anal fissure [33]. Using a GI disease-specific QOL questionnaire, the GIQLI [34], a similar result has been found with patients undergoing surgery for recurrent fistula [35], suggesting that the benefits of successful surgery may outweigh the risks of reduced continence.…”
Section: Discussionsupporting
confidence: 83%
“…Bouchard et al [17] found anal stenosis in 23 patients out of 633 patients in the one-year outcome of open haemorrhoidectomy. F. Greca et al [18] found that, repeated treatment was necessary in 13 patients after phenol injection compared with only 4 following rubber band ligation (P<0·05).…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques exist, however most are associated with the same complications [10]. A recent study evaluated the 1-year outcome of open haemorrhoidectomy in 633 patients, 36% involving the Milligan and Morgan procedure and 64% the Leopold Bellan procedure [15]. Immediate complications were reported in 6.9% of patients, including urinary retention, faecal impaction, secondary haemorrhage requiring haemostasis and local infection.…”
Section: Discussionmentioning
confidence: 99%